A calculus problem by Rocco Dalto

Calculus Level 4

The solution to the differential 1 2 ( d y d x ) 2 a y = 1 2 \dfrac{1}{2} \left(\dfrac{dy}{dx}\right)^2 - \dfrac{a}{y} = -\dfrac{1}{2} can be expressed as the arc x = f ( θ ) x = f(\theta) , y = g ( θ ) y = g(\theta) , and the curve passes thru the origin so that x = y = 0 x = y = 0 , when θ = 0 \theta = 0 , and x ( π ) = a π , y ( π ) = 2 a x(\pi) = a\pi , \: y(\pi) = 2a , and f ( θ ) > 0 f'(\theta) > 0 for all ( 0 < θ < π ) (0 < \theta < \pi) .

The area of the surface formed by rotating the above arc x = f ( θ ) x = f(\theta) , y = g ( θ ) y = g(\theta) about the x x -axis from θ = 0 \theta = 0 to θ = π \theta = \pi can be expressed as m n π a 2 \dfrac{m}{n}\pi a^2 , where m m and n n are coprime positive integers.

Find m + n m + n .


The answer is 35.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Nov 21, 2016

1 2 ( d y d x ) 2 a y = 1 2 \dfrac{1}{2} * (\dfrac{dy}{dx})^2 - \dfrac{a}{y} = -\dfrac{1}{2} \implies

d y d x = 2 a y y x = y 2 a y d y \dfrac{dy}{dx} = \sqrt{\dfrac{2a - y}{y}} \implies x = \int \sqrt{\dfrac{y}{2a - y}} \: dy

Let u 2 = y 2 u d u = d y u^2 = y \implies 2u \: du = dy \implies

x = 2 u 2 2 a u 2 d u x = 2 * \int \dfrac{u^2}{\sqrt{2a - u^2}} \: du

Let u = 2 a s i n θ d u = 2 a c o s θ d θ u = \sqrt{2a} sin\theta \implies du = \sqrt{2a} cos\theta \: d\theta \implies

x = 2 a ( 1 c o s ( 2 θ ) ) d θ = 2 a ( θ 1 2 s i n ( 2 θ ) ) = a ( 2 θ s i n ( 2 θ ) ) + C . x = 2a * \int (1 - cos(2\theta)) \: d\theta = 2a * (\theta - \dfrac{1}{2} sin(2\theta)) = a * (2\theta - sin(2\theta)) + C.

x ( θ ) = 0 C = 0 X = a ( 2 θ s i n ( 2 θ ) ) x(\theta) = 0 \implies C = 0 \implies X = a * (2\theta - sin(2\theta))

x = u 2 = 2 a s i n 2 θ = a ( 1 c o s ( 2 θ ) ) . x = u^2 = 2a * sin^2\theta = a * (1 - cos(2\theta)).

Replacing 2 θ 2\theta by θ \theta we obtain:

x = a ( θ s i n θ ) x = a * (\theta - sin\theta) , y = a ( 1 c o s θ ) y = a * (1 - cos\theta)

Now we rotate the cycloid about the x - axis from θ = 0 \theta = 0 to θ = π \theta = \pi .

d x d θ = a ( 1 c o s θ ) \dfrac{dx}{d\theta} = a * (1 - cos\theta) and d y d θ = a s i n θ \dfrac{dy}{d\theta} = a * sin\theta \implies

Area A = 2 π a 2 0 π ( 1 c o s θ ) 2 ( 1 c o s θ ) d θ A = 2\pi * a^2 * \int_{0}^{\pi} (1 - cos\theta) \sqrt{2(1 - cos\theta)} \: d\theta =

8 π a 2 0 π s i n 2 ( θ 2 ) s i n ( θ 2 ) d θ 8\pi * a^2 * \int_{0}^{\pi} sin^2(\dfrac{\theta}{2}) * sin(\dfrac{\theta}{2}) \: d\theta

8 π a 2 0 π ( 1 c o s 2 ( θ 2 ) ) s i n ( θ 2 ) d θ = 8\pi * a^2 * \int_{0}^{\pi} (1 - cos^2(\dfrac{\theta}{2})) * sin(\dfrac{\theta}{2}) \: d\theta =

8 π a 2 0 π s i n ( θ 2 ) c o s 2 ( θ 2 ) s i n ( θ 2 ) d θ = 8\pi * a^2 * \int_{0}^{\pi} sin(\dfrac{\theta}{2}) - cos^2(\dfrac{\theta}{2}) * sin(\dfrac{\theta}{2}) \: d\theta =

8 π a 2 ( 2 c o s ( θ 2 ) + 2 3 c o s 3 ( θ 2 ) ) 0 π = 32 3 π a 2 = m n π a 2 8\pi * a^2 * (-2 cos(\dfrac{\theta}{2}) + \dfrac{2}{3} * cos^3(\dfrac{\theta}{2}))|_ {0}^{\pi} = \dfrac{32}{3}\pi * a^2 = \dfrac{m}{n}\pi * a^2 \implies

m + n = 35. m + n = 35.

Note: Replacing 2 θ 2\theta by θ \theta does not change the surface area.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...